2011
DOI: 10.1021/jf2025677
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Methods for Metabolite Profiling of Virus- and Phytoplasma-Infected Plants of Echinacea purpurea

Abstract: This study was focused on the effects of virus and phytoplasma infections on the production of Echinacea purpurea (L.) Moench secondary metabolites, such as caffeic acid derivatives, alkamides, and essential oil. The identification of caffeic acid derivatives and alkamides was carried out by means of high-performance liquid chromatography-diode array detection (HPLC-DAD), HPLC-electrospray ionization-mass spectrometry (ESI-MS), and MS(2). Quantitative analysis of these compounds was carried out using HPLC-DAD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
30
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 36 publications
11
30
0
2
Order By: Relevance
“…The petals showed contractions, deformations and mottling [10,11]. In 2009, CMV-infected plants showed stunting; leaves with yellow mosaics, ring, line patterns and malformations; small fl owers with pale stripes on red petals [12]. Mo reover, Italian scientists have studied genetic modifi cations of the CMV isolates, taken from aromatic, offi cinal and ornamental plants in the Northern Italy.…”
Section: Cucumber Mosaic Virus CMVmentioning
confidence: 99%
“…The petals showed contractions, deformations and mottling [10,11]. In 2009, CMV-infected plants showed stunting; leaves with yellow mosaics, ring, line patterns and malformations; small fl owers with pale stripes on red petals [12]. Mo reover, Italian scientists have studied genetic modifi cations of the CMV isolates, taken from aromatic, offi cinal and ornamental plants in the Northern Italy.…”
Section: Cucumber Mosaic Virus CMVmentioning
confidence: 99%
“…A HPLC method (INA-Institute for Nutraceutical Advancement method 106.000) from NSF (National Science Foundation) International (Ann Arbor, MI, USA) is accessible as well. Clear chicoric acid mass spectra examples can be found in Shiga et al (2009) and Mulinacci et al (2001); mother and fragmented masses have been reported in numerous papers with various MS settings, so one of these references can be used for comparison with a comparable analysis (Mulinacci et al, 2001; Baur et al, 2004; Lee and Scagel, 2009; Shiga et al, 2009; Pellati et al, 2011; Ribas-Agusti et al, 2011; Carazzone et al, 2013). …”
Section: Identification Synthesis and Biosynthesis Chicoric Acidmentioning
confidence: 99%
“…Pathogens can have a negative impact on plant growth but may increase phenolic accumulation. For example pathogen attack (cucumber mosaic virus and phytoplasma-prokaryote) decreased chicoric acid levels in E. purpurea roots (Pellati et al, 2011). Foliar application of carboymethyl chitin glucan (a fungal elicitor produced by Penicillium ) increased production of chicoric acid in roots of E. purpurea (Hudec et al, 2007).…”
Section: Plant × Growing Environment Interactionsmentioning
confidence: 99%
“…Other compounds that increased in infected leaves were β-ocimene (I = 3.463%, H = 2.304%), trans-caryophyllene (I = 1.828%, H = 0.853%), cis-geraniol (Nerol) (I = 0.887%, H= 0.330%), and β-myrcene (I = 0.670%, H = 0.434%). Phytoplasma infection is known to change the cell metabolism leading to an increase of certain compounds and the reduction of others [4,[25][26][27].…”
Section: Resultsmentioning
confidence: 99%